The danger imperative : violence, death, and the soul of policing - Sierra-Arévalo, Michael (Columbia University Press, 2024)
" Policing is violent. And its violence is not distributed equally: stark racial disparities persist despite decades of efforts to address them. Amid public outcry and an ongoing crisis of police legitimacy, there is pressing need to understand not only how police perceive and use violence but also why. With unprecedented access to three police departments and drawing on more than 100 interviews and 1,000 hours on patrol, The Danger Imperative provides vital insight into how police culture shapes officers' perception and practice of violence. From the front seat of a patrol car, it shows how the institution of policing reinforces a cultural preoccupation with violence through academy training, departmental routines, powerful symbols, and officers' street-level behavior. This violence-centric culture makes no explicit mention of race, relying on the colorblind language of "threat" and "officer safety." Nonetheless, existing patterns of systemic disadvantage funnel police hyperfocused on survival into poor minority neighborhoods. Without requiring individual bigotry, this combination of social structure, culture, and behavior perpetuates enduring inequalities in police violence. A trailblazing, on-the-ground account of modern policing, this book shows that violence is the logical consequence of an institutional culture that privileges officer survival over public safety." -- Provided by publisher
Keywords: Police brutality -- United States.; Police-community relations -- United States.; Danger -- United States.; Equality -- United States.; Brutalités policières -- États-Unis.; Relations police-collectivité -- États-Unis.; Danger -- États-Unis.; SOCIAL SCIENCE / Penology